2010
DOI: 10.1186/1477-7525-8-136
|View full text |Cite
|
Sign up to set email alerts
|

Quality of Life as reported by children and parents: a comparison between students and child psychiatric outpatients

Abstract: BackgroundDuring the recent decade, a number of studies have begun to address Quality of Life (QoL) in children and adolescents with mental health problems in general population and clinical samples. Only about half of the studies utilized both self and parent proxy report of child QoL. Generally children with mental health problems have reported lower QoL compared to healthy children. The question whether QoL assessment by both self and parent proxy report can identify psychiatric health services needs not de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
42
0
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 40 publications
(46 citation statements)
references
References 36 publications
3
42
0
1
Order By: Relevance
“…In this study our results are in accordance with other studies reporting a discrepancy between the self-report and proxy report in different clinical and general population studies (Theunissen et al, 1998;Chang and Yeh, 2005;Yeh and Chang, 2005;Jozefiak et al, 2008Jozefiak et al, , 2009Jozefiak et al, , 2010. However, our study also showed that comparing QoL child vs. proxy report directly in studies of children surviving cancer could be misleading without including a control group.…”
Section: Child and Parent Proxy Reportssupporting
confidence: 91%
See 1 more Smart Citation
“…In this study our results are in accordance with other studies reporting a discrepancy between the self-report and proxy report in different clinical and general population studies (Theunissen et al, 1998;Chang and Yeh, 2005;Yeh and Chang, 2005;Jozefiak et al, 2008Jozefiak et al, , 2009Jozefiak et al, , 2010. However, our study also showed that comparing QoL child vs. proxy report directly in studies of children surviving cancer could be misleading without including a control group.…”
Section: Child and Parent Proxy Reportssupporting
confidence: 91%
“…The ILC was translated into Norwegian according to international standards and approved by the original authors. The Norwegian version of the ILC for adolescents (aged 12e18 years and may be used up to 20 years) and their parents have shown satisfactory reliability (Jozefiak et al, 2008(Jozefiak et al, , 2010. Both adolescent (self-report) and parent (proxy report for children and adolescents from 4 to 20 years) versions were used in the present study.…”
Section: Quality Of Life (Qol)mentioning
confidence: 99%
“…That only parents reported reduced QoL in children with comorbid conditions might be due to the general tendency of children to rate their QoL with a more optimistic view than their parents, as seen in other studies. In studies of parent-child agreement on QoL, parents of children in non-clinical samples tend to report higher QoL scores than their children (Jozefiak et al, 2010;, while parents of children with disorders tend to under-estimate QoL compared with their children. In Lack and coworkers' (2009) study, parents generally rated QoL lower than their children did, suggesting that young people may minimize the impact of their condition on QoL.…”
Section: Comorbidity Is Associated With Reduced Qolmentioning
confidence: 99%
“…This may lead to biased results, because it is possible that children who have both a mental disorder and reduced HRQOL are more likely to be referred to or treated in a clinic, compared to children with mental disorders without a marked reduction in HRQOL [25]. For example, in a recently published study, referred psychiatric outpatients exhibited lower HRQOL scores than students with equivalent levels of emotional and behavioral problems [52]. Hence, studies that use population-based approaches should be considered to validate the results found among clinical samples.…”
Section: Limitations Of Existing Studies and Recommendations For Furtmentioning
confidence: 99%